Artificial intelligence : A modern approach - Russell, Stuart J.; Norvig, Peter (Englewood Cliffs, New Jersey : Prentice-Hall, 1995)
For one/two-semester, undergraduate or graduate-level courses in Artificial Intelligence.The most comprehensive, up-to-date introduction to the theory and practice of artificial intelligence.
I. ARTIFICIAL INTELLIGENCE. 1. Introduction. 2. Intelligent Agents. II. PROBLEM-SOLVING. 3. Solving Problems by Searching. 4. Informed Search Methods. 5. Game Playing. III. KNOWLEDGE AND REASONING. 6. Agents that Reason Logically. 7. First-order Logic. 8. Building a Knowledge Base. 9. Inference in First-Order Logic. 10. Logical Reasoning Systems. IV. ACTING LOGICALLY. 11. Planning. 12. Practical Planning. 13. Planning and Acting. V. UNCERTAIN KNOWLEDGE AND REASONING. 14. Uncertainty. 15. Probabilistic Reasoning Systems. 16. Making Simple Decisions. 17. Making Complex Decisions. VI. LEARNING. 18. Learning from Observations. 19. Learning with Neural Networks. 20. Reinforcement Learning. 21. Knowledge in Learning. VII. COMMUNICATING, PERCEIVING, AND ACTING. 22. Agents that Communicate. 23. Practical Communication in English. 24. Perception. 25. Robotics. VIII. CONCLUSIONS. 26. Philosophical Foundations. 27. AI: Present and Future.
Includes index.
Keywords: ARTIFICIAL INTELLIGENCE